The Effect of Different Delivery Strategies And Locus Of Control On Procedural Learning Outcomes - Triretnoningrum, Alfin Niken; Degeng, Made Duananda Kartika; Setyosari, Punaji (JKTP: Jurnal Kajian Teknologi Pendidikan, 2025)
This study aims to explore the influence of delivery strategies on students' procedural learning outcomes on anecdotal text learning, with locus of control as the moderator variable. This study used a quasi-experimental method with a two-to-two factorial design and involved sixty-four students who were divided into two classes: experimental (using video media) and control (using textbooks). Data analysis was carried out using the Two-Way ANOVA technique. The results show that video-based learning strategies significantly improve student learning outcomes compared to textbooks. Students with internal control loci had higher average learning outcomes than students with external control locus, although the influence of the control locus was not statistically significant. In addition, no significant interaction was found between delivery strategies and control loci on learning outcomes. This study recommends the use of multimedia-based strategies to optimize learning outcomes, especially for procedural materials. These findings also provide practical insights to consider the characteristic factors of each student, such as the control locus, in choosing a more effective and relevant learning method. Abstrak Penelitian ini bertujuan untuk mengeksplorasi pengaruh strategi penyampaian terhadap hasil belajar prosedural siswa pada pembelajaran teks anekdot, dengan locus of control sebagai variabel moderator. Penelitian ini menggunakan metode kuasi-eksperimental dengan desain faktorial dua kali dua dan melibatkan enam puluh empat siswa yang dibagi menjadi dua kelas: eksperimental (menggunakan media video) dan kontrol (menggunakan buku ajar). Analisis data dilakukan dengan menggunakan teknik Two-Way ANOVA. Hasil penelitian menunjukkan bahwa strategi pembelajaran berbasis media video secara signifikan meningkatkan hasil belajar siswa dibandingkan dengan buku ajar. Siswa dengan lokus kontrol internal memiliki hasil belajar rata-rata yang lebih tinggi daripada siswa dengan lokus kontrol eksternal, meskipun pengaruh lokus kontrol tidak signifikan secara statistik. Selain itu, tidak ditemukan interaksi yang signifikan antara strategi penyampaian dan lokus kontrol pada hasil belajar. Penelitian ini merekomendasikan penggunaan strategi berbasis multimedia untuk mengoptimalkan hasil pembelajaran, terutama untuk materi prosedural. Temuan ini juga memberikan wawasan praktis untuk mempertimbangkan faktor karakteristik masing-masing siswa, seperti lokus kontrol, dalam memilih metode pembelajaran yang lebih efektif dan relevan.